Phylogeographical studies in disjunct populations of symplocos laurina wall. using cytoplasmic PCR-RFLP approach - Banu, Sofia; Lagu, Meena D.; Gupta, Vidya S. (Tree Genetics & Genomes, 2010)
Genetic variation, haplotype relationships, and potential regions of diversity in Symplocos laurina Wall. (Symplocaceae), a montane tree species from India, have been tested using molecular and biogeographical data to infer phylogeographic patterns. The polymerase chain reaction-restriction fragment length polymorphism technique was used to determine the chloroplast (cp) and mitochondrial (mt) DNA haplotypes of 218 individuals from 12 populations, collected from Northeast India (NEI), which is a part of Indo-Burma biodiversity hotspot, and South India, which includes the Western Ghats (WG), another biodiversity hotspot from India and Eastern Ghats (EG). Nine cpDNA (chlorotypes) and 24 mtDNA haplotypes (mitotypes) were identified; the WG region was identified as the most diverse for chlorotypes and the NEI region for mitotypes. Although a strong population differentiation was observed, phylogeographic structure was found to be absent for both the genomes. The haplotype network revealed the presence of two main lineages: NEI-WG lineage and EG lineage, largely without overlapping distributions. The study tests two hypotheses, namely vicariance and dispersal, to understand the distribution of plants in India. The population structure of S. laurina strongly suggests the persistence of the species in putative refugial areas preglaciation and further establishment of other populations of S. laurina from these refugial populations.
Keywords: Cytoplasmic genome; Genetic diversity; Phylogeography